Parasite-host relationships of warble fly (Oedemagena tarandi L.) and reindeer (Rangifer tarandus L.) - Solomakha, A. I. (Rangifer, 1990)
The interspecific relations of the warble fly and reindeer have assumed a character of a lenient parasitism. Many researchers note that almost all reindeer are infested by warble fly and reindeer and they also note that almost all domestic reindeer are more heavily infested than wild reindeer. Infestation rates in young domestic reindeer range from 26 to 324 larvae per animal and in young wild reindeer from 15 to 126 larvae per animal. Mature, domestic reindeer are infested with 25 to 417 larvae per animal and in mature wild reindeer the infestation ranges from 38 to 94 larvae per animal. Infestation rates decrease with age.